2010
DOI: 10.1182/blood-2009-10-250225
|View full text |Cite
|
Sign up to set email alerts
|

End-of-life experience of children undergoing stem cell transplantation for malignancy: parent and provider perspectives and patterns of care

Abstract: The end-of-life (EOL) experience of children who undergo stem cell transplantation (SCT) may differ from that of other children with cancer. To evaluate perspectives and patterns of EOL care after SCT, we surveyed 141 parents of children who died of cancer (response rate, 64%) and their physicians. Chart review provided additional information. Children for whom SCT was the last cancer therapy (n ‫؍‬ 31) were compared with those for whom it was not (n ‫؍‬ 110). SCT parents and physicians recognized no realistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
67
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 51 publications
6
67
0
4
Order By: Relevance
“…In our study, and consistent with prior reports, 23,34,35 the majority of patients who died received LST prior to death, and the transition period from attempts at curative treatment to death was brief. Studies have reported the primary goal of cancer-directed therapies was cure and/or life extension, even in the EOL period.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In our study, and consistent with prior reports, 23,34,35 the majority of patients who died received LST prior to death, and the transition period from attempts at curative treatment to death was brief. Studies have reported the primary goal of cancer-directed therapies was cure and/or life extension, even in the EOL period.…”
Section: Discussionsupporting
confidence: 79%
“…Studies have reported the primary goal of cancer-directed therapies was cure and/or life extension, even in the EOL period. 14,34 These findings, along with the results of our study, may suggest a different pattern of EOL care that is desired by HSCT patients undergoing a risky procedure in the pursuit of cure. If providing LST and seeking cure until death is the preference of HSCT patients, physicians must seek to balance respect for patient choices with honest communication about the limits of medicine, with the need for increased attention to symptom control and the lessening of suffering.…”
Section: Discussionmentioning
confidence: 50%
“…18,36 Evolving personal states (coping skills, spirituality, hope), 16,33 social support, 36 family cohesion, spousal communication, and changes in socioeconomic status 37 were all associated with caregiver resilience, as were modifiable aspects of the medical experience (caregiver perceptions of the experience and associated stressors). 5,[38][39][40][41] Parents with better insight into their child's prognosis were better able to set realistic goals 42,43 or prepare for their child's death; 43,44 such abilities may encourage more positive psychosocial outcomes. 11,[42][43][44][45] Finally, much of the clinical literature related resilience to positive psychosocial outcomes, a lack of adverse outcomes (comparative normalcy), or those patients and families who go on to lead psychologically healthy or productive lives.…”
Section: Literature Reviewmentioning
confidence: 99%
“…5,[38][39][40][41] Parents with better insight into their child's prognosis were better able to set realistic goals 42,43 or prepare for their child's death; 43,44 such abilities may encourage more positive psychosocial outcomes. 11,[42][43][44][45] Finally, much of the clinical literature related resilience to positive psychosocial outcomes, a lack of adverse outcomes (comparative normalcy), or those patients and families who go on to lead psychologically healthy or productive lives. [46][47][48] Many cited specific psychosocial outcomes as evidence for or against resilience; however, the timing of the outcome and its…”
Section: Literature Reviewmentioning
confidence: 99%
“…3 Very recently, Wolfe and colleagues reported on a large study comprising 141 children who died of cancer, and they concluded that HSCT is associated with significant suffering and less opportunity to prepare for end-of-life. 7 Larger samples and studies with longer follow-up may help us to understand whether bereaved parents of children treated with HSCT may be at a greater risk of psychological and physical morbidity than other bereaved parents in the long-term perspective. The aim of the present study was to assess the long-term psychological consequences in parents whose child had had a HSCT due to his or her malignancy before death.…”
Section: Introductionmentioning
confidence: 99%